Anti-inflammatory Activity and Major Compounds of the Traditional Thai Medicines, Triphala, Trikatuk, and their Combined Formulae - Nuaeissara, Supaluck; Itharat, Arunporn; Pipatrattanaseree, Weerachai; Panthong, Sumalee (Science & Technology Asia, 2022)
Inflammation is a common factor leading to pathogenesis of several chronic diseases, including cardiovascular diseases, chronic metabolic syndromes, arthritis, and cancer. Trikatuk and Triphala are traditional poly-herbal preparations widely used in Ayurvedic and Thai traditional medicine. The present study aimed to investigate various combinations of these preparations and their mixing methods to optimize product efficacy. Samples were extracted by boiling in water and maceration with 95% ethanol. All samples were tested for inhibitory effects on LPS-induced nitric oxide (NO) production, and on LPS-induced prostaglandins (PGE2) from RAW 264.7 cells. Contents of major markers of the extracts were analyzed with HPLC. Trikatuk ethanolic extract showed anti-inflammatory activity through inhibition of NO production but Triphala had no effect on neither NO nor PEG2 production. A combined formula of Triphala and Trikatuk (1:1) provided moderate anti-inflammatory activity in both pathways. The present study reported the anti-inflammatory effects of various combinations and mixing methods of Trikatuk and Triphala, the results of which could be used to develop optimal combinations for future use as dietary supplements and other health products.